Outcomes Between Stemmed and Stemless Total Shoulder Arthroplasty: A Systematic Review and Meta-analysis of Randomized Controlled Trials. (2nd November 2022) - Looney, Austin M.; Day, Jonathan; Johnson, John L.; Johnston, Peter S.
Abstract : Introduction: Both stemmed and stemless designs for total shoulder arthroplasty (TSA) have demonstrated efficacious outcomes for the surgical treatment of primary glenohumeral joint osteoarthritis. The purpose of this systematic review and meta-analysis was to compare the clinical outcomes of stemmed versus stemless TSA in randomized controlled trials. We hypothesized that there would be no differences in Constant Score (CS), range of motion, or adverse events, such as periprosthetic fracture and/or revision surgery. Methods: Using the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines, a systematic review of the literature was done using MEDLINE, SPORTDiscus, Cumulative Index to Nursing and Allied Health Literature, Cochrane Central Registry of Controlled Trials, Embase, and Web of Science databases. Outcomes of interest included CS, range of motion, and adverse events (periprosthetic fracture and revision). Summary effect estimates of the mean difference between stemmed and stemless TSA for each outcome were estimated in random effects models. Results: The search yielded 301 articles with 4 appropriate for qualitative analysis, including the results of 229 stemmed and 358 stemless TSAs. No significant difference was observed in postoperative CS ( P = 0.36), forward flexion ( P = 0.93), abduction ( P = 0.30), or external rotation ( P = 0.34) between stemmed and stemless TSA. No significant difference was observed in change in CS ( P = 0.27), forward flexion ( P = 0.25), or external rotation ( P = 0.74). A change in abduction was significantly different between stemmed and stemless TSA (standardized mean difference = −0.64; 95% confidence interval, −1.20 to −0.08) in favor of stemmed TSA ( P = 0.02), attributed to preoperative differences. No significant difference was observed in periprosthetic fractures ( P = 0.07) or revision ( P = 0.90). Conclusion: TSA with stemless versus stemmed humeral components was not associated with notable differences in functional and clinical outcomes. No difference was observed between stemmed and stemless designs in postoperative forward flexion, abduction, or external rotation. Similarly, there was no difference in change in forward flexion or external rotation. A markedly greater improvement in abduction was observed with stemmed TSA, likely due to the lower preoperative motion in the stemmed cohort in one of the studies. No differences were observed between stemmed and stemless designs in the rate of humeral fracture or risk of revision. Level of Evidence: Level II; systematic review and meta-analysis of prospective randomized controlled trials.